2021
DOI: 10.3390/polym13101591
|View full text |Cite
|
Sign up to set email alerts
|

PCL/Andiroba Oil (Carapa guianensis Aubl.) Hybrid Film for Wound Healing Applications

Abstract: Developing a biomimetic material to wound care is an emerging need for the healing process. Poly (ε-caprolactone) (PCL) is a polymer with the necessary dressing’s requirements often used in medicine. Their surface, physic-chemical and biological properties can be modified by adding bioactive compounds, such as andiroba seed oil (Carapa guianensis). This Amazonian natural plant has medicinal and pharmacological properties. For this purpose, PCL polymeric films incorporated with andiroba oil were investigated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 64 publications
(72 reference statements)
4
18
0
Order By: Relevance
“…Milk et al [ 20 ] found that the addition of oil to chitosan membranes provided a decrease in the contact angle. However, a similar study by Silva et al [ 22 ] found different results, demonstrating that the introduction of andiroba oil into the membrane composition confers greater hydrophobic power to the material.…”
Section: Resultsmentioning
confidence: 93%
“…Milk et al [ 20 ] found that the addition of oil to chitosan membranes provided a decrease in the contact angle. However, a similar study by Silva et al [ 22 ] found different results, demonstrating that the introduction of andiroba oil into the membrane composition confers greater hydrophobic power to the material.…”
Section: Resultsmentioning
confidence: 93%
“…Silva et al [ 45 ] observed that the addition of andiroba oil decreases the number and size of pores, as the concentration of oil in poly-based polymeric film (ε-caprolactone) (PCL), as well as no oil retention on the surface of the films, which may indicate a good interaction of the compound PCL/andiroba. However, the changes that occurred in the structure of chitosan with the incorporation of oils depending on the molecular structure of the polymer and its chemical interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The results from the second heating were adopted to eliminate the thermal history [34]. The degree of crystallinity could be obtained by the following formula [35]:…”
Section: Characterization Of Pcl Porous Microspheresmentioning
confidence: 99%